ESTUDO DA HIDRODINÂMICA DAS BAÍAS DE ILHA GRANDE E SEPETIBA - Mordente, Thiago Zamprogno (2020)
Hydrodynamics is extremely important for several activities that take place in an estuary. Additionally, the application of computational fluid dynamics for a better understanding of the circulation is a recurring practice today. In this context, the pres